Embodied memories, embedded healing: new ecological perspectives from East Asia - Liu, Xinmin; Huang, Peter I-min (Environment and society, 2021)
"Embodied Memories, Embedded Healing foregrounds the East Asian cultural beliefs and practices that shape the environmental consciousness of the twenty-first century. In highlighting such influences, this anthology also foregrounds the closely related new and exciting directions in ecocriticism"--